2010
DOI: 10.1038/emboj.2010.300
|View full text |Cite
|
Sign up to set email alerts
|

c-IAP1 and UbcH5 promote K11-linked polyubiquitination of RIP1 in TNF signalling

Abstract: Ubiquitin ligases are critical components of the ubiquitination process that determine substrate specificity and, in collaboration with E2 ubiquitin-conjugating enzymes, regulate the nature of polyubiquitin chains assembled on their substrates. Cellular inhibitor of apoptosis (c-IAP1 and c-IAP2) proteins are recruited to TNFR1-associated signalling complexes where they regulate receptor-stimulated NF-jB activation through their RING domain ubiquitin ligase activity. Using a directed yeast two-hybrid screen, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
259
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(272 citation statements)
references
References 45 publications
11
259
0
2
Order By: Relevance
“…Although Cezanne was reported to inhibit NF-κB signaling through removing K63-linked polyubiquitin chains from RIP1 [24,25], Bremm et al [40] found that Cezanne preferentially hydrolyzes K11-linked polyubiquitin chains. Interestingly, a recent study reported that K11-linked polyubiquitin chains of RIP1 can also serve as a platform for recruitment of NEMO and participate in TNF-α-stimulated NF-κB activation [41]. In this respect, investigating the selectivity of Cezanne for K11-or K63-linked ubiquitin chains may reveal a novel regulatory mechanism of NF-κB signaling and facilitate the discovery of new therapeutic targets for cancer treatment and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Although Cezanne was reported to inhibit NF-κB signaling through removing K63-linked polyubiquitin chains from RIP1 [24,25], Bremm et al [40] found that Cezanne preferentially hydrolyzes K11-linked polyubiquitin chains. Interestingly, a recent study reported that K11-linked polyubiquitin chains of RIP1 can also serve as a platform for recruitment of NEMO and participate in TNF-α-stimulated NF-κB activation [41]. In this respect, investigating the selectivity of Cezanne for K11-or K63-linked ubiquitin chains may reveal a novel regulatory mechanism of NF-κB signaling and facilitate the discovery of new therapeutic targets for cancer treatment and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…6 Within this complex, RIPK1 and other proteins are rapidly conjugated with Ub chains of various types. [7][8][9][10] These Ub chains act as scaffolds for the recruitment and activation of the TAK1-binding protein 2/3 (TAB2/3)-TGF-bactivated kinase 1 (TAK1) complex and the inhibitor of nuclear factor-kB (NF-kB) kinase (IKK) complex (NEMO-IKKa-IKKb), These authors contributed equally to this work. …”
mentioning
confidence: 99%
“…6 Within this complex, RIPK1 and other proteins are rapidly conjugated with Ub chains of various types. [7][8][9][10] These Ub chains act as scaffolds for the recruitment and activation of the TAK1-binding protein 2/3 (TAB2/3)-TGF-bactivated kinase 1 (TAK1) complex and the inhibitor of nuclear factor-kB (NF-kB) kinase (IKK) complex (NEMO-IKKa-IKKb), which subsequently leads to the activation of the mitogenactivated protein kinases and canonical NF-kB signaling pathways that collectively drive transcription of genes that prevent cell death and sustain inflammation. Accordingly, when the NF-kB response is inhibited, either genetically or by the use of the general translation inhibitor cycloheximide (CHX), TNFR1 ligation switches from a pro-survival to a pro-apoptotic response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9] c-IAP1/2 and LUBAC target RIP1 for K11, K63 and linear polyubiquitination priming RIP1 for the recruitment of two kinase-containing complexes, namely, TAK1/TAK1-binding protein 1 (TAB1)/TAB2 and NEMO/ inhibitor of NF-κB kinase α (IKKα)/IKKβ. 5,[10][11][12][13] Ultimately, activation of IKKβ leads to the phosphorylation and proteasomal degradation of IκBα and the nuclear translocation of NF-κB, a pathway defined as the classical, or the canonical, NF-κB pathway. [14][15][16] Besides its role in the activation of NF-κB, the dissociation of complex I from TNFR1 triggers the recruitment of Fas-associated protein with death domain (FADD) and caspase-8 to form a cytosolic death complex, initially defined as complex II.…”
mentioning
confidence: 99%